تأثير النقد السوسيولوجي للنص الروائي الجزائري في القارئ - بن قانة, حفيظة (Revues faculté des lettres et des langues, 2018)
Abstract: This Rubbing shoulders with students recently indicates that the majority of them suffer from nervousness in the way of analysis, a conflict in adapting their aspirations and a chaos when raising questions. They were diverted from following their reality because of their dependence on mass media and to compute which has limited their capacity of apprehension and productivity. The one who follows this situation may notice that its cause is due to the precedent steps of education, especially the high school level where the student is at age that allows him to build himself and then his reality. These causes and others necessitate a deep reflection in literary contexts introduced in high school education, especially the Algerian novelist text being considered as a plant which contains the most important fundamental means to form the student’s educational, intellectual, gustatory, and instructive capacity which help him create his own social and literang world asit snovld be Thus, it is important to shed light, in the future, on the strategy of choosing Algerian novelist texts and the ways of their reception so as to build a person with a sense of responsibility. These texts should represent the real world he lives in, establish the basics of civilization and respond to his new aspirations in addition to help him achieve balance between organizing his thinking and developing his imagination. On this basis, I thought that my interposition would cope with the presence of the Algerian novelist text and its analysis in making a real productive reader/student. الملخص تشير معايشة راهن طلبة قسمنا مؤخرا إلى القول بأن معظمهم يعاني توترا في طريقة التحليل وصراعا في تكييف طموحه وفوضى في إثارة التساؤلات؛ حيث غربته تبعيته لوسائل الاعلام عن مباشرة واقعه، وحدّ اتكاله على أجهزة الكبيوتر من قدرته الاستعابية والانتاجية.     ولعلّ المتتبع لمسار هذه الوضعية يلاحظ مرجعها إلى مراحل تعليمه السابقة، خاصة منها مستوى التعليم الثانوي إذ يصبح الطالب في سن تؤهله لصناعة ذاته ومن ثم واقعه.     هذه الأسباب وغيرها، تستدعي التأمل العميق في النصوص الأدبية المُدرجة في مقررات التعليم الثانوي، خاصة منها النص الروائي الجزائري بوصفه المصنع الذي يحوي أهم الوسائل الأساسية لتكوين قدرة الطالب التربوية الفكرية والذوقية والتثقيفية التي تسهم في الأخذ بيده ليدخل معترك تشكيل واقعه الاجتماعي والأدبي من بابه الواسع.    وعليه، غدا من الضرورة تسليط الضوء على استراتيجية اختيار النصوص الروائية الجزائرية وطرائق تلقيها بهدف بناء فرد ذي حس مسؤول، فهذه النصوص يجب أن تمثل واقعه وتؤسس لمقوماته الحضارية وتستجيب لتطلعاته المتجددة، وتساعده في تحقيق التوازن بين تنظيم فكره وتنمية خياله.     بناء على هذا تتناول هذه المقالة مدى حضور النص الروائي الجزائري وقراءاته في إعداد قارئ/طالب فعلي منتج؟